Smart and Sustainable Food Technologies - Sehgal, Shalini; Singh, Barinderjit; Sharma, Vasudha (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents a comprehensive view of emerging smart technologies in various food processing sectors. Specifically, it covers smart technologies applied in food production, food manufacturing, food packaging, storage, distribution, and food supply chain. Contributing authors are the key scientists with diverse backgrounds in either industry or academia. The book contains four parts with four chapters each, presenting recent smart technologies developed in their respective areas. Part I primarily focuses on the recent smart food production innovations such as precision agriculture, vertical farming, automation, robotics , livestock technology, modern greenhouse practices, artificial intelligence, and block chain that dramatically increase the quality of raw materials for the food industry. Part II provides the current knowledge and developments related to the recent smart technologies in manufacturing pertaining to various food sectors, non-thermal food preservation technologies, and 3D printing, developed for the food manufacturing industries that improve the organoleptic and nutritional quality, enhance chemical and microbial safety, as well as cost-effectiveness and convenience of processed foods. Part III covers smart technologies to ensure food safety in the supply chain, with monitoring and surveillance of food contamination, use of IoT and blockchain for food traceability and neural network approach for risk assessment. Part IV provides expert opinions on using smart technologies for minimizing waste and maximizing co-product recovery in food processing; upcycling technologies in food and sustainable value stream mapping in the food industry. This book will be a useful resource to graduate/undergraduate students and researchers in advanced food technology, practicing technologists/engineers in the food and related industries, food packaging industry, entrepreneurs and other scientists and technologists in smart and sustainable processes who seek information on design and development of these processes.
Chapter 1. Smart and Sustainable Food Production Technologies -- Chapter 2. Smart Technologies in Livestock Farming -- Chapter 3. Prospects of Smart Aquaculture in Indian Scenario: A New Horizon in the Management of Aquaculture Production Potential -- Chapter 4. Smart and automatic milking systems: Benefits and prospects -- Chapter 5. Smart Technologies in Food Manufacturing -- Chapter 6. Non- thermal Food Preservation Technologies -- Chapter 7. 3D Printing: Technologies, Fundamentals and Applications in Food Industries -- Chapter 8. Smart Food Packaging Systems -- Chapter 9. Smart Monitoring and Surveillance of Food Contamination -- Chapter 10. Neural Network Approach for Risk Assessment along the Food Supply Chain -- Chapter 11. Waste Minimization and Management in Food Industry -- Chapter 12. Co-Product Recovery in Food Processing -- Chapter 13. Upcycling Technologies in the Food Industry -- Chapter 14. Sustainable Value Stream Mapping in the Food Industry.
Keywords: Food science; Food Science; Food Engineering